2023
DOI: 10.3390/su151310584
|View full text |Cite
|
Sign up to set email alerts
|

Transcending Time and Space: Survey Methods, Uncertainty, and Development in Human Migration Prediction

Abstract: As a fundamental, holistic, and strategic issue facing human society, human migration is a key factor affecting the development of countries and cities, given the constantly changing population numbers. The fuzziness of the spatiotemporal attributes of human migration limits the pool of open-source data for human migration prediction, leading to a relative lag in human migration prediction algorithm research. This study expands the definition of human migration research, reviews the progress of research into h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 97 publications
1
1
0
Order By: Relevance
“…and S.F. [51,56,59,62], this study confirmed the relationship between the moderating role of K.M. This provides a deeper understanding of how K.M.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…and S.F. [51,56,59,62], this study confirmed the relationship between the moderating role of K.M. This provides a deeper understanding of how K.M.…”
Section: Discussionsupporting
confidence: 81%
“…methods are crucial for fostering innovation and gaining a sustainable competitive edge in today's corporate landscape. There is an increasing emphasis on developing strategies for generating, using, and sharing knowledge within firms [13,[60][61][62].…”
Section: Knowledge Managementmentioning
confidence: 99%